P3.433 Cost-Effectiveness of Enhanced Syphilis Screening Among HIV-Positive Men Who Have Sex with Men. (13th July 2013) - Tuite, A; Machina, M; Burchell, A; Bayoumi, A; Fisman, D
Abstract : Background: Syphilis co-infection has increased substantially among HIV-positive men who have sex with men (MSM). Screening rates in this population remain below recommended guidelines for screening frequency. We evaluated the cost-effectiveness of increasing the frequency and coverage of screening to recommended levels in HIV-positive MSM receiving HIV care. Methods: We developed a Markov cohort model to evaluate the cost-effectiveness of enhanced syphilis screening in a cohort of HIV-positive MSM with baseline characteristics (including current screening coverage) reflective of men enrolled in an observational cohort study of individuals receiving medical care for HIV in Ontario, Canada. We compared usual care (50% of the population screened annually) to enhanced screening (100% screened every 3 months). Model parameters were from the health literature and the observational cohort database. Both strategies incorporated a treponemal screening test followed by a confirmatory non-treponemal test; test characteristics varied at each stage of syphilis infection. Outcomes were quality-adjusted life years (QALYs), lifetime costs (2011 Canadian dollars), and incremental cost-effectiveness ratios. The model used the perspective of a public health care payer and a lifetime time horizon, with a base case discount rate of 5% applied to future costs and outcomes. Results: Compared to usual care, enhanced screening increased quality-adjusted life expectancy by 0.016 QALYs and decreased costs by 1437 per person. Enhanced screening remained the preferred strategy when the incidence of syphilis was above 0.5 per 100 person-years. Findings were robust in wide-ranging deterministic sensitivity analyses, including assumptions around reduced adherence to screening recommendations. In probabilistic sensitivity analysis, the probability that enhanced screening was cost-effective exceeded 85%, assuming a willingness-to-pay of up to 50, 000 per QALY. Conclusions: Our model suggests that in populations with moderate to high rates of syphilis acquisition, enhanced syphilis screening alongside HIV medical care has the potential to improve health and save costs.